Asymptomatic Dysplasia Epiphysealis Hemimelica of the Shoulder in a Skeletally Mature Patient with Normal Function - Vincenzo Giordano; Marcos Giordano; Carolina Giordano; José Giordano; Renato Mendonça; Hilton Augusto Koch (Case Reports in Radiology)
Dysplasia epiphysealis hemimelica is a rare osteocartilaginous overgrowth syndrome of bone epiphysis, mostly encountered in the lower limbs of immature skeleton patients. We report a case of proximal humerus presentation in an adult male, with neither articular involvement nor clinical dysfunction. This case highlights the importance of stratification into intra- and extra-articular lesions, as this distinction ultimately influences both symptoms and treatment outcome. In addition, the case highlights the importance of specific imaging modalities, such as CT and MR images, which provide excellent anatomic location of the lesion, adequate extension of cartilaginous components, exact status of articular cartilage, and accurate assessment of neighboring structures, such as vessels, nerves, ligaments, tendons, and muscles. The imaging features are described, the relevant literature is reviewed, and salient features are discussed.